Stretching ANATOMY - Nelson, Arnold G., 1953-; Kokkonen, Jouko, 1950- (Human Kinetics, 2021)
"This guide combines step-by-step instructions for performing stretches and full-color anatomical illustrations highlighting the primary muscles and surrounding structures engaged. The third edition highlights stretches for the major body joint areas. Each stretch includes a list of stretched muscles and specific stretch notes to help learn the best way to execute the stretch. The book also includes stretching programs for daily mobility and flexibility, a program shown to lower blood glucose, and sport-specific stretching routines"--